Diretrizes para a modelagem BIM de elementos e objetos orientados ao LOD 200 e LOD 300 para orçamentação - Flavia Camelo Freire (2019)
n order to a project for construction to be successful, it is essential to budget it to verify the viability of building it. This activity, even today, relies on the use of traditional methods, based on 2D data, under which quantity takeoff is performed manually. With BIM quantity takeoff can be conducted automatically, as long as its elements and objects are developed under a pre-established standard according to the intended level of development (LOD) and are coded based on a classification system aimed at budgeting. In this sense, this research work is aimed at proposing guidelines to establish a modeling process for architectural and structural projects towards developing models suitable for cost estimation in BIM, while assessing the criteria of accuracy of the information obtained, feasibility of interoperability between BIM platform software programs and the modeling effort at different LODs. It was founded on the Design Science Research methodology, under which work phases are set up so that a model oriented to LOD 200 is generated and later upgraded to LOD 300, according to pre-defined modeling requirements. In this way, reliability of the quantitative data obtained through both models can be assessed from the comparison with the original data, developed based on 2D information. The results show that it is possible to automatically retrieve reliable quantitative data for significant items at each LOD; thus, an average difference of 2.65% was found between the quantity takeoffs from the LOD 200 model and 7.11% from the LOD 300 model compared to the reference data. Nevertheless, interoperability was assured through the use of a plug-in created in the modeling software for direct export to the cost estimation software. The modeling effort made when maturing the model from a generic LOD to an accurate LOD is worth, since it allows for project improvements throughout the process; however, this cost-benefit ratio must be weighed by the user based on the type of information intended for retrieval from the model. Finally, an important contribution of this research work is the elaboration of a BIM modeling process for budgeting.